Neural dependency parser with biaffine attention - Fankhauser, Peter; Do, Bich-Ngoc; Kupietz, Marc (Universität, 2023)
This resource contains the code of the dependency parser used in the paper: Fankhauser, et al. (2020). "Evaluating a Dependency Parser on DeReKo". The parser is a re-implementation of the neural dependency parser from Dozat and Manning (2017). In addition, we include two pre-trained models on the German dataset of the SPMRL 2014 Shared Task with slightly different POS tags.
Gesehen am 20.11.2023
Keywords: Forschungsdaten; Datenbank